CLASS 1 COMMUNITY INSTITUTIONS BANDAR LAMPUNG ARE USING THE DEVELOPMENT OF INDEPENDENCE TO GROW ENTREPRENEURIAL SKILLS - Saragih, Alexandro Junior; Muhammad, Ali (PT. Altin Riset Publishing, 2024)
This research aims to analyze the implementation coaching independence for prisoners to grow their ability to entrepreneurship in correctional Class 1 Bandar Lampung. The research methods used are qualitative and were implemented for one month in July and September. During the study results obtained, implementation coaching independence in Correctional Institutions Class I Bandar Lampung for establishing ability entrepreneurship is still not adequate. This is influenced by factors inhibitory, namely: limitations in budget, lack of means and feelings, lack of expertise in his field, as well as a feeling of laziness that influences the inhabitant. Therefore, it's expected that Prison Class I Bandar Lampung increases the program for more independence, which is effective for citizens and builds more spirit in the follow-activity entrepreneurship carried out by prisons in Class I Bandar Lampung.